Fully solar powered Doncaster Sheffield Airport: Energy evaluation, glare analysis and CO2 mitigation. (June 2021) - Sher, Farooq; Hazafa, Abu; Marintseva, Kristina; Rasheed, Tahir; Ali, Usman; Rashid, Tazien; Babu, Amal; Khzouz, Martin
Highlights: Feasibility study of 12 MWp PV power plant was examined at Doncaster Sheffield Airport, UK. Average monthly and annual energy was observed as 1, 034.31 and 12, 411.59 MWh respectively. CO2 reduction per month and annual were noted as 880, 189 and 10, 562, 270 kg respectively. The maximum CUF of 21.67 and 21.04% was reported in June and July respectively. A 12 MWp solar photovoltaic (PV) power plant reported an average performance ratio of 82.59%. Abstract: The solar photovoltaic cells received special attention during the past few years due to their rapid renewability consideration, particularly in international airports because of sustainability and high cost of fossil fuel. The present study aims to evaluate the feasibility performance of a novel 12 MWp capacity solar photovoltaic (PV) power plant at Doncaster Sheffield Airport, UK and to develop a mathematical model to provide a greater understanding of glare from solar panels and subsequently outline methods to avoid its effects. SISIFO and Global Solar Atlas software (GSA) simulations were used to obtain the results. Results reported that the proposed plant produced average energy of 1, 034.31 MWh monthly and 12, 411.69 MWh annually. The maximum electricity production was observed in May, June, and July as 1, 772.71, 1, 872.32, and 1, 818.25 MWh, with 20.51, 21.67, and 21.04% of Capacity Utilization Factor (CUF), respectively. The average energy yield per month was achieved as 2585.74 kWh/kWp with an average performance ratio of 82.59%. Results also showed that 12 MWp PV plant at DSA reduced an average CO2  emission of 10, 562, 270 kg (11, 642.90 tons) annually. The results revealed that glaring is very unlikely to occur throughout the year; however, winter period produced the lowest trajectory of reflected light. Overall, the proposed solar plant at Doncaster Sheffield airport (DSA) was found to be feasible and generates almost double electricity of overall energy demand (6, 951.55 MWh) at Doncaster Sheffield airport. However, it is recommended that the excessive produced energy during summer could be transfer into the national grid, which would be returned during the winter season to facilitate PV plant.